2012
DOI: 10.1007/s00253-012-4198-6
|View full text |Cite
|
Sign up to set email alerts
|

Yeast genes involved in sulfur and nitrogen metabolism affect the production of volatile thiols from Sauvignon Blanc musts

Abstract: Two volatile thiols, 3-mercaptohexan-1-ol (3MH), and 3-mercaptohexyl-acetate (3MHA), reminiscent of grapefruit and passion fruit respectively, are critical varietal aroma compounds in Sauvignon Blanc (SB) wines. These aromatic thiols are not present in the grape juice but are synthesized and released by the yeast during alcoholic fermentation. Single deletion mutants of 67 candidate genes in a laboratory strain of Saccharomyces cerevisiae were screened using gas chromatography mass spectrometry for their thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…It is important to note that most functional studies have been conducted by deletion of IRC7 S in different S. cerevisiae laboratory strain backgrounds (33)(34)(35). Even though we, and others, have shown that the Irc7p S has no activity toward substrates such as cysteine or Cys-4-MMP, the truncated protein and/or the genomic locus itself may be functionally important in yeast.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is important to note that most functional studies have been conducted by deletion of IRC7 S in different S. cerevisiae laboratory strain backgrounds (33)(34)(35). Even though we, and others, have shown that the Irc7p S has no activity toward substrates such as cysteine or Cys-4-MMP, the truncated protein and/or the genomic locus itself may be functionally important in yeast.…”
Section: Discussionmentioning
confidence: 84%
“…The biological role of IRC7 is not well established, as many functional studies have been conducted in strain backgrounds containing the inactive version of IRC7 (33)(34)(35). While IRC7 was originally suggested to be involved in DNA metabolism since the null mutant causes increased rates of recombination between homologous chromosomes (33), its role as cysteine desulfhydrase also points out to an involvement in the regulation of cysteine homeostasis (32).…”
mentioning
confidence: 99%
“…Nitrogen availability during fermentation has an impact on the release of varietal thiols, but the effect is not well characterized. Thus, opposite effects of nitrogen addition (as ammonium) have been reported, either increasing (Harsch and Gardner, 2013) or decreasing the release of thiols (Subileau et al, 2008) depending on the study.…”
Section: Introductionmentioning
confidence: 98%
“…In addition the following strains from the School of Biology Sciences of the University of Auckland were used because of their good sporulation: BC186 (natural isolate from oak trees), SK1 (= NCYC 3265, lab strain isolated from soil; Liti et al, 2009), Zymaflore F15 (commercial wine yeast; Harsch and Gardner, 2013), and Lesaffre Ethanol Red ® (industrial fermentation).…”
Section: Yeast Strainsmentioning
confidence: 99%